Toxoplasma on the Brain: Understanding Host-Pathogen Interactions in Chronic CNS Infection - Sushrut Kamerkar; Paul H. Davis (Journal of Parasitology Research)
Toxoplasma gondii is a prevalent obligate intracellular parasite which chronically infects more than a third of the world’s population. Key to parasite prevalence is its ability to form chronic and nonimmunogenic bradyzoite cysts, which typically form in the brain and muscle cells of infected mammals, including humans. While acute clinical infection typically involves neurological and/or ocular damage, chronic infection has been more recently linked to behavioral changes. Establishment and maintenance of chronic infection involves a balance between the host immunity and parasite evasion of the immune response. Here, we outline the known cellular interplay between Toxoplasma gondii and cells of the central nervous system and review the reported effects of Toxoplasma gondii on behavior and neurological disease. Finally, we review new technologies which will allow us to more fully understand host-pathogen interactions.